Single-session endoscopic fundoplication after peroral endoscopic myotomy (POEM+F) for prevention of post gastroesophageal reflux – 1-year follow-up study - Bapaye, Amol; Dashatwar, Parag; Dharamsi, Siddharth; Pujari, Rajendra; Gadhikar, Harshal (Endoscopy, 2021)
Background Peroral endoscopic myotomy (POEM) is an established treatment for achalasia cardia; however, post-POEM gastroesophageal reflux (GER) remains a significant problem. Concomitant endoscopic fundoplication following POEM (POEM + F) was recently described to reduce post-POEM GER. This single-center study reports short-term outcomes of POEM + F.Methods This was a retrospective analysis of a prospectively maintained database of patients undergoing POEM + F. Abstracted data included demographics, achalasia type, pre-POEM Eckardt score, prior therapy, follow-up. Follow-up assessment was 3-monthly for 1 year and included post-POEM Eckardt score, GerdQ score, wrap integrity and esophagitis on esophagogastroduodenoscopy, and pH studies. GER was defined according to Lyon Consensus.Results 25 patients underwent POEM + F (mean age 40.1 years [standard deviation (SD) 13.7]; 12 females). POEM + F was technically successful in 23/25 (92.0 %). Significant dysphagia improvement was seen in all 25 patients (mean pre- and post-POEM Eckardt scores 8.21 [SD 1.08] and 0.1 [SD 0.3], respectively; P = 0.001). Mean total procedure and fundoplication times were 115.6 (SD 27.2) minutes and 46.7 (SD 12.4) minutes, respectively; times reduced significantly after the initial five cases. Median follow-up was 12 months (interquartile range [IQR] 9–13). Intact wrap was seen in 19/23 (82.6 %). GER (abnormal esophageal acid exposure time [EAET]) was seen in 2/18 (11.1 %) and there was one reported GerdQ > 8. Borderline GER (asymptomatic grade A esophagitis, normal EAET) was identified in 4/22 (18.2 %). Three (12.0 %) minor delayed adverse events occurred but required no intervention.Conclusions POEM + F was safe and reproducible. At 12 months’ follow-up, incidence of post-POEM + F GER was low and acceptable.